Household responses to trade shocks - Aitor Irastorza-Fadrique; Peter Levell; Matthias Parey (Institute for Fiscal Studies (IFS), 2023)
We use large-scale panel data from linked decadal censuses in England and Wales to study the responses of both individuals and their partners to rising Chinese import competition in the 2000s. We test whether partners provide insurance against lost household earnings by increasing labour supply. We find that both own and partner responses to the shock vary significantly by gender. Men in households exposed to import competition respond by increasing labour force participation at older ages, and by moving into solo self-employment. This is true both in response to their own trade exposure, and as an 'added worker effect' when their partner is exposed to the shock. By contrast, we find no such response for women, who do not increase labour supply if their male partners were initially employed in exposed industries. In general, self-employment appears to act as an employment buffer for men but not women. The impacts of import competition on partnering and family dissolution also differ according to the gender of those affected: for women below 45, but not men, exposure to the trade shock reduces the likelihood of divorce and of living with a new partner. Overall, our findings underscore the importance of investigating household responses, and the self-employment margin, to fully understand the effects of trade shocks.
Keywords: D10; F14; F16; F61; J12; 330; Import Competition; Families; Labour Supply; Added-Worker Effects